2017
DOI: 10.1098/rsif.2017.0405
|View full text |Cite
|
Sign up to set email alerts
|

A light-dependent magnetoreception mechanism insensitive to light intensity and polarization

Abstract: Billions of migratory birds navigate thousands of kilometres every year aided by a magnetic compass sense, the biophysical mechanism of which is unclear. One leading hypothesis is that absorption of light by specialized photoreceptors in the retina produces short-lived chemical intermediates known as radical pairs whose chemistry is sensitive to tiny magnetic interactions. A potentially serious but largely ignored obstacle to this theory is how directional information derived from the Earth's magnetic field ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 77 publications
1
47
0
Order By: Relevance
“…To make the problem tractable, we reduce the dimension of the system by grouping the cells contained in spherical caps of half-angle ξ = 0.5° to form a smaller number of ‘grouped magnetoreceptor cells’. The cells within each group have such similar positions and orientations that they will have almost identical average singlet yields, Φ S (Worster et al ., 2017). Each group is treated as a single receptor cell that absorbs the total number of photons that would impinge on the constituent cells during the integration time.…”
Section: Magnetoreceptor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…To make the problem tractable, we reduce the dimension of the system by grouping the cells contained in spherical caps of half-angle ξ = 0.5° to form a smaller number of ‘grouped magnetoreceptor cells’. The cells within each group have such similar positions and orientations that they will have almost identical average singlet yields, Φ S (Worster et al ., 2017). Each group is treated as a single receptor cell that absorbs the total number of photons that would impinge on the constituent cells during the integration time.…”
Section: Magnetoreceptor Cellsmentioning
confidence: 99%
“…The double-cone photoreceptor cells have been proposed as the most likely location of the magnetoreceptors (Worster et al ., 2017; Günther et al ., 2018). They are arranged on an approximately hexagonal lattice in the retina with a nearest neighbour separation of 7 µm (Kram et al ., 2010), giving an average of one double cone per 40 µm 2 of retina.…”
Section: Magnetoreceptor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas type I and II CRY functions are well characterized, CRY4 proteins are poorly explored and existing studies offer contradictory information regarding their molecular mechanisms (9, 11, 12). However, recent studies have suggested that CRY4 is ideally positioned in the double cones (13), where it could be oriented to differentiate between light intensity, polarization, and magnetic field changes (13, 14). Furthermore, CRY4 seems to be the only bird CRY that binds FAD at physiological conditions (3, 13, 15), which is a definitive requirement for the ability to function as light-dependent magnetoreceptors for seasonal migration.…”
mentioning
confidence: 99%
“…Simply put, a light stimulus on a cryptochrome, a photoreceptive molecule, induces the formation of a transient radical pair (i.e., pair of molecules with unpaired electrons) that is sensitive to external magnetic fields. This mechanism is well studied in birds (reviewed in Wiltschko and Wiltschko, 2019) and has been recently considered as the leading hypothesis, since it is supported by chemical, physical, and biological facts (see details in Worster et al, 2017).…”
Section: Mechanisms Of Magneto and Electroreceptionmentioning
confidence: 90%